Linkage between permafrost distribution and river runoff changes across the Arctic and the Tibetan Plateau (2020)
River runoff in the Arctic and the Tibetan Plateau(TP) change significantly in recent decades. However, the mechanisms of the physical processes of permafrost river runoff change remain uncertain across large scale. This study investigated the mainstreams and tributaries of main Arctic and TP rivers dominated by permafrost and assessed the linkage between hydrological regime change and permafrost. The results show that the effects of permafrost on river runoff are highly dependent on the permafrost coverage of a watershed. For the past decades, the majority of the Arctic and TP basins showed increased discharge, while all of the studied basins showed increased baseflow, with faster increasing speed than total discharge.Both total discharge and baseflow annual change rate(ΔQ and ΔBF) increased with permafrost coverage, indicating the increments of streamflow are enhanced with high permafrost coverage. Meanwhile, the annual change of precipitation showed weak connection with total discharge and baseflow change. The high permafrost coverage basins showed high annual maximum/minimum discharge ratio(Qmax/Qmin), while the Qmax/Qminchanged slightly in low permafrost cover basins. Our results highlight the importance of permafrost coverage on streamflow regime change for permafrost basins across the northern hemisphere. Due to these linkage between permafrost extent and runoff regime change and the increasing changes of permafrost, more attention should be paid to the change of hydrological processes in permafrost-underlain basins.